The Level of Nutritional Understanding among Physical Education and Health Recreation Students at Nusantara PGRI University Kediri - Phamungkas, Jhohan Surya; Zawawi, M Anis; Burstiando, Rizki (CV. Nusantara Sporta, 2024)
Nutrition understanding is the ability to comprehend and explain dietary patterns, sources of nutrition, and their benefits for the body. A lack of knowledge about daily nutritional needs often makes it difficult for students to establish healthy eating habits. Nutrition plays a crucial role in enhancing the quality of Human Resources (HR). Students, who are in a productive age, need to have a good understanding of nutrition to maintain their health. This study aims to assess the level of nutritional understanding among Physical Education students at Universitas Nusantara PGRI Kediri. Using a quantitative approach and descriptive survey method, the study involved 88 students selected through simple random sampling. Data were collected via a 30-question questionnaire about nutritional understanding, and categorized into three levels: good, adequate, and poor. Data analysis was conducted descriptively. The results showed that out of 88 students, 56 (64%) had good nutritional understanding, 30 (34%) had adequate understanding, and 2 (2%) had poor understanding. Most students at Universitas Nusantara PGRI Kediri demonstrated good nutritional understanding, indicating the need for continued nutrition education to ensure that all students have adequate knowledge of the importance of nutrition in daily life